The DISCOURSE OF SEWAKA DHARMA IN THE TEXT OF KAKAWIN NĀGARAKṚTĀGAMA - Ni'mah, Mamluatun; I Nyoman Suarka; I Gede Oeinada (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This research aims to determine the form of Mpu Prapañca's sewaka dharma discourse towards King Hayam Wuruk and the Majapahit Kingdom in the Kakawin Nāgarakṛtāgama text. Sewaka dharma discourse is a discourse about devotion or service on the path of truth towards something. This research uses Ferdinand de Saussure's semiotic theory to determine the signifying and signified aspects of Mpu Prapañca's sewaka dharma discourse towards King Hayam Wuruk and the Majapahit Kingdom in the Kakawin Nāgarakṛtāgama text. Next, at the stage of analyzing the data using descriptive analysis methods with content analysis techniques. Then, at the stage of presenting the results of data analysis using informal methods with inductive deductive techniques. The data source for this research is the Kakawin Nāgarakṛtāgama text. The results of this research are Mpu Prapañca's journey in dedicating himself to King Hayam Wuruk by following wherever King Hayam Wuruk went and dedicating himself to the Majapahit Kingdom by writing about its beauty and splendor in a literary work, especially the Kakawin Nāgarakṛtāgama text. So you can find out about Mpu Prapañca's sewaka dharma discourse to King Hayam Wuruk and the Majapahit Kingdom.